2020
DOI: 10.1007/s10686-020-09670-z
|View full text |Cite
|
Sign up to set email alerts
|

CHESS: An innovative concept for high-resolution, far-UV spectroscopy

Abstract: The space ultraviolet (UV) is a critical astronomical observing window, where a multitude of atomic, ionic, and molecular signatures provide crucial insight into planetary, interstellar, stellar, intergalactic, and extragalactic objects. The next generation of large space telescopes require highly sensitive, moderate-to-high resolution UV spectrograph. However, sensitive observations in the UV are difficult, as UV optical performance and imaging efficiencies have lagged behind counterparts in the visible and i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…Hoadley et al pointed out that sensitive observations in ultraviolet conditions are difficult because UV optical performance and imaging efficiency lag behind their visible and infrared counterparts [10]. Because UV optical performance and imaging efficiency are not as good as the corresponding characteristics of visible light and infrared light, it is difficult to make accurate observations in ultraviolet conditions.…”
Section: Uv Bandmentioning
confidence: 99%
“…Hoadley et al pointed out that sensitive observations in ultraviolet conditions are difficult because UV optical performance and imaging efficiency lag behind their visible and infrared counterparts [10]. Because UV optical performance and imaging efficiency are not as good as the corresponding characteristics of visible light and infrared light, it is difficult to make accurate observations in ultraviolet conditions.…”
Section: Uv Bandmentioning
confidence: 99%
“…Nowadays, it is thought that some starting prebiotic molecular materials may be widely distributed throughout the Universe (Sandford et al, 2020) and the search for the biosignatures is one of the main goals of current and future space missions involving the next generation of space telescopes (JWST, ARIEL, OST, HabEx, LUVOIR) (Lasne, 2021), spectrometers onboard of spacecrafts or rovers (Flasar et al, 2005;Vago et al, 2017;Vago et al, 2018;Williford et al, 2018) or the new class of high-resolution spectrometers operating in the UV region, (i.e., CHESS) (Hoadley et al, 2020) allowing observations beyond capacities of present-day facilities such as the Hubble Space Telescope (HST). In the case of essential molecules of life, it has been shown that carbonaceous meteorites contain a wide range of extraterrestrial nucleobases (Callahan et al, 2011), but uracil is still the only pyrimidine base formally reported in such meteorites (Stoks and Schwartz, 1979).…”
Section: Introductionmentioning
confidence: 99%